Factor Analysis Infertility Events in Poly Gynekology Hospitals dr. H. Slamet Martodirdjo Pamekasan - A'yun, Qurratul; Suhita, Byba Melda; Laila, Siti Farida Noor (Journal for Research in Public Health, 2020)
The growing assumption in the community is that infertility is caused by women, whereas in men it can also occur at infertility of 20-40%, in women 30-55%, a combined factor of 35% and causes that cannot be identified are 5-15%. The cause of infertility is caused by women and men, the causes also vary. Ranging from sexual problems to genetics. The purpose of the study was to determine the factors that influence the incidence of infertility in the obstetrical Poly of RSUD Dr.H. Islamet Martodirdjo Pamekasan. Quantitative research design with cross sectional approach. The study was conducted on September 17 to November 23, 2018 with a population of 108 couples and a sample of 85 couples with a sample random sampling technique. Data collection of independent variables with questionnaires and dependent variables by means of medical records. Data analysis using logistic regression test. Based on the results of logistic regression statistics, the wife's physical activity variables were p value 0.484 and husband's p value 0.628, wife's nutritional status p value 0.651 and husband's p value 0.392, wife's smoking p value 0.999 and husband's p value 0.028, wife's diet p value 0.306 and husband p value 0.138 then infertile incidence simultaneously influenced by the variable significantly p value 0,000 at α = 0.05. Infertility events are jointly influenced by physical activity, nutritional status, smoking and diet, and can be influenced by other factors related to reproductive organs in couples of childbearing age. Factors that greatly influence infertility in husbands are smoking. Because cigarette smoke is a chemical that changes DNA, so it is not able to fertilize the egg, slowing down the motility sperm to reach the egg so fertilization does not occur